THE USE OF GENOTYPING TO SELECT DESIRED-TYPE ANIMALS - Alexander I. Surov; Svetlana N. Chumachenko; Arslan A. Omarov; Ekaterina D. Karpova; Darya D. Evlagina; Evgeny N. Chernobai; Nina I. Efimova; Sergey S. Bobryshov (Siberian Journal of Life Sciences and Agriculture, 2023)
Modern sheep breeding should be based on the production of high quality sheep products. Knowing the limits of animal productivity potential allows to manage the breeding process in the most effective way. Applying PCR-RFLP method makes it possible to identify allelic variants of genes associated with quantitative and qualitative characteristics of animals. By identifying different polymorphic variations and their phenotypic manifestations, one can create and replenish a database for managing the genetic progression of breeding-significant traits.